Pituitary as a Source of HCG: Residual Levels After Bilateral Testicular Tumor Removal. (April 2019) - Santen, Richard; Hasan, Farhad; Thoren, Katie; Farooki, Azeez
Context . Challenging clinical scenario in which elevated β-human chorionic gonadotropin (HCG, subsequently termed HCG) levels suggested occult tumor metastases after removal of bilateral testicular cancers and metastases from them and as well as after chemotherapy. Case Report . A 22-year-old male, post excision of bilateral testicular tumors, who had no imaging or clinical evidence of residual tumor but an elevated HCG raising the question of the presence and location of occult tumor metastases. Clinical Questions . Does luteinizing hormone (LH) cross-react with HCG in current assays? What levels of testosterone and estradiol are necessary to suppress LH and follicle-stimulating hormone (FSH) in a male patient with bilateral orchiectomy, and therefore lacking inhibin? Does the pituitary secrete HCG and under what circumstances? Assessment . Current HCG assays no longer cross-react with LH as did prior assays, but the presence of heterophile antibodies and other factors such as biotin can still cause false positive HCG levels. In the chronic post-orchiectomy state, the pituitary is relatively resistant to LH and FSH suppression by testosterone. The pituitary secretes HCG in very small amounts unless interruption of negative feedback results in high LH and FSH whereupon HCG levels become elevated. Clinical Conclusion . A GnRH antagonist suppressed both LH and HCG in this patient indicating that the elevated HCG was secreted by the pituitary and not by occult tumor metastases. Further credence for this conclusion resulted from the lack of a progressive increase in HCG levels over a 4-year period of follow-up and from no evidence of metastatic tumors on serial imaging.